Perlindungan Hukum Korban Tindak Kekerasan Dalam Pacaran Ditinjau Dari Perspektif Viktimologi Dan Psikososial - Fransiska Novita Eleanora; Zulkifli Ismail; Melanie Pita Lestari (Jurnal Kajian Ilmiah, 2023)
The purpose of this study was to identify and describe violence in a relationship from a victimological perspective and the psychosocial implications of violence in a relationship. The problems that will be discussed in this paper are how is Dating Violence according to Victimology Perspective?; and what are the Psychosocial Implications of Dating Violence?. The research method used in this study is a normative juridical method using a statutory approach and a case approach. Based on the research conducted, it is known that dating violence is an act of violence against couples who are not married, including physical, emotional, economic violence and activity restrictions. These acts of violence often occur, but have not received much attention so that they are sometimes neglected in society. In fact, dating violence requires attention due to its broad nature and impact on women's lives in particular and society in general. This type of violence has its roots in cultural factors that place women in an unequal position in relation to men.